2008
DOI: 10.1108/13552540810862055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hybrid mould on moulded parts properties

Abstract: Purpose -This paper aims to emphasize compared experimental analysis of influence of hybrid and classic moulds on the properties of moulded parts and the processing parameters. Such analysis enables optimization of processing parameters in case of the hybrid mould. Design/methodology/approach -Representative moulded part and appropriate hybrid and classic moulds have been designed and manufactured. The experimental work contains a screening design and the main central composite design for analysing the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…The impact loads and, in particular, high strain rate tensile impact, can be critical issues in FFF parts and, in general, for plastic materials [21,22]. However, limited research has been done in understanding the impact mechanical behaviour of FFF 3D printed parts and, to the authors’ knowledge, no research work has been done about the tensile impact strength of FFF.…”
Section: Introductionmentioning
confidence: 99%
“…The impact loads and, in particular, high strain rate tensile impact, can be critical issues in FFF parts and, in general, for plastic materials [21,22]. However, limited research has been done in understanding the impact mechanical behaviour of FFF 3D printed parts and, to the authors’ knowledge, no research work has been done about the tensile impact strength of FFF.…”
Section: Introductionmentioning
confidence: 99%
“…Under the action of the laser beam's thermal energy, the powdery material softens and this results in mutual sintering of material particles and fusion of the newly applied layer of powder with the previously sintered layer (Pilipovic et al, 2010;Godec et al, 2008;Drstvenšek et al, 2008).…”
Section: Selective Laser Sinteringmentioning
confidence: 99%
“…In SLS procedure, the laser beam is directed by a mirror and marks the cross-section of the product on the powdery material located on the working platform. Under the action of the laser beam's thermal energy, the powdery material softens and this results in mutual sintering of material particles and fusion of the newly applied layer of powder with the previously sintered layer (Pilipovic et al, 2010;Godec et al, 2008;Drstvenšek et al, 2008).…”
Section: Selective Laser Sinteringmentioning
confidence: 99%
“…They have found that the most important parameters affecting each mechanical property vary at different levels for the two mold materials. Godec et al [8] sought to approximate the mass, dimension and tensile impact strength among PP moldings obtained in different tool materials through the packing pressure, melt temperature and injection time parameters. The tool materials were the LaserForm A6, obtained in an indirect metal laser sintering process, infiltrated with bronze, and the steel 40CrMn-MoS8 6, obtained by machining.…”
Section: Introductionmentioning
confidence: 99%